(untitled) (International Journal of Scientific Trends, 2026)
This scientific article provides a comprehensive analysis of the system of public administration bodies in the field of ecology and their competencies. The study examines the institutional structure of environmental governance, the distribution of powers, and the effectiveness of inter-agency cooperation. Particular attention is given to the role of digital technologies, public participation, and economic instruments in implementing environmental policy. Based on international experience, recommendations for improving environmental governance are proposed. The findings highlight the need to modernize public administration to ensure environmental safety and achieve sustainable development.